The Impact of Customer Service, Network Quality, Promotions, and Corporate Social Responsibility on Brand Image: An Empirical Study of the Telecommunication Industry in Guinea" - Conde, Ousmane; Wangbenmad, Chutima (AMAR (Andalas Management Review), 2024)
This study investigates the impact of customer service, network quality, promotions, and corporate social responsibility (CSR) on brand image in the telecommunication industry in Guinea. Given the competitive nature of the sector and the growing demand for reliable services, companies must understand the key drivers that shape consumer perceptions of their brand. Using a quantitative research approach, data were collected through surveys from telecommunication customers in Guinea. The findings reveal that customer service are the most significant factors influencing brand image, while network quality, promotions and CSR efforts also play a positive but lesser role. The study suggests that telecommunication companies in Guinea can enhance their brand image by improving customer service, upgrading network quality, implementing creative promotional activities, and engaging in meaningful CSR initiatives. These insights are valuable for managers aiming to strengthen their competitive position and improve customer retention in a dynamic market.